Elements of critical reading in EFL teachers’ instructions - Ilyas, Hamzah Puadi (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2023)
Reading instructions should go a bit beyond ‘explicit question’ to facilitate students’ critical thinking. What it means by ‘explicit question’ is question whose answer can be found in the text explicitly. This research, therefore, aimed to investigate EFL teachers’ reading instructions to find out to what extend the instructions contained the elements of critical reading. Twenty-seven EFL teachers participated by listing all the activities they had given to students throughout their teaching career. All the activities were collected, and similar activities were combined. There were a total of ninety-nine instructions. The activities were then compared to critical reading framework to find out which elements they belonged to. Findings showed that teachers’ reading instructions only belonged to such categories as identifying, analyzing, summarizing, and guessing. Aside from that, the instructions for the four categories were the same. It appeared that EFL teachers lacked creativity and innovative ideas. There were still elements or categories of critical reading that had not yet been utilized or explored. These findings prompted the inclusion of critical reading instruction design skills in teacher education. After all, critical thinking has long been emphasized in national education as a means of developing responsible citizens and avoiding becoming a victim of false information.